Nigerian University and its mandate in a changing world - Anyebe, Adam Adem (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2014)
In the context of an evolving competitive and private sector-driven economy, the Nigerian university is expected to advance itself in academic programmes, research and innovation towards academic excellence and world-class status. However, the Nigerian university system does not appear to have attained this status. What is responsible for this state of affairs? This paper, therefore, attempt to assess the system via its mandate to be world-class in a rapidly changing world. The study employed secondary data source. The ultimate objective of any university is to strive to attain academic excellence by ensuring quality teaching, research and public service. This can only be achieved when the university uses innovative curriculum and pedagogical methods under conducive circumstances. This study however, revealed that the exponential increase in the number of universities and student enrollment without necessary funds has brought about dearth of other resources and facilities such as run-down infrastructure, inadequate laboratories, and ill-equipped libraries, all contributing to the decline in the university system. The aspiration of the Nigerian university to attain world-class status is yet to be realized. For the country’s university system to attain this status, it needs to be systematically planned with a profound change in the curriculum.